2016
DOI: 10.1016/j.jamcollsurg.2015.12.044
|View full text |Cite
|
Sign up to set email alerts
|

Are Surgeons Being Paid Fairly by Medicaid? A National Comparison of Typical Payments for General Surgeons

Abstract: These findings call into question the fairness of MCD reimbursement for general surgery services in the United States. This discount to MCR could act as a disincentive for surgeons to care for some patients, based on the state of residence. These unexplained discounts could have considerable long-term effects for patients dependent on the MCD program. Our study should act as a stimulus for states to examine their payment methodologies to provide more uniform and fairer payments for surgical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 2 publications
2
14
0
Order By: Relevance
“…Although some state-level variation is expected because of differences in population, policies, historic policy, and labor costs, the magnitude of these variations may lead to disparities among states in quality and access to care. In 2015, Medicaid reimbursement for procedures performed by general surgeons deviated from Medicare by over $1,000 in both positive and negative directions 2 . In a health-care environment increasingly geared toward rewarding value, reimbursement should reflect how states value physicians' work.…”
mentioning
confidence: 99%
“…Although some state-level variation is expected because of differences in population, policies, historic policy, and labor costs, the magnitude of these variations may lead to disparities among states in quality and access to care. In 2015, Medicaid reimbursement for procedures performed by general surgeons deviated from Medicare by over $1,000 in both positive and negative directions 2 . In a health-care environment increasingly geared toward rewarding value, reimbursement should reflect how states value physicians' work.…”
mentioning
confidence: 99%
“…In its current form, Medicaid financing does offer participating states some flexibility with regard to how participating physicians are reimbursed, with the overarching aim of optimizing health care access for beneficiaries. 43 Although remuneration parity with Medicare and commercial payers is not feasible, increasing reimbursement rates to levels that encourage the enlistment of an array of care providers such as plastic surgeons will considerably improve disparities in IBR use. In a recent study, organization-level characteristics such as available staffing, system inefficiencies, and limited abilities to invest in care improvement activities were identified as potential drivers of the delivery of higher cost, lower quality care.…”
Section: Discussionmentioning
confidence: 99%
“…At the policy level, prior research has suggested reduced Medicaid physician reimbursement rates compared with Medicare and commercial payers as a cause of lower access for Medicaid enrollees. 43 Although remuneration parity with Medicare and commercial payers is not feasible, increasing reimbursement rates to levels that encourage the enlistment of an array of care providers such as plastic surgeons will considerably improve disparities in IBR use. [38][39][40] Economic incentives are acknowledged to be a powerful determinant of physician behavior.…”
Section: Original Articlementioning
confidence: 99%
“…Finally, to account for potential variation in the actual cost of the additional imaging by facility, state, and payer, we performed a sensitivity analysis varying the cost by 75% and 150%. These differences were determined by the reported magnitude of differences in commercial insurance and Medicaid reimbursement compared to Medicare reimbursement 14,15…”
Section: Methodsmentioning
confidence: 99%